2021
DOI: 10.1186/s13662-021-03588-2
|View full text |Cite
|
Sign up to set email alerts
|

Operational matrices based on the shifted fifth-kind Chebyshev polynomials for solving nonlinear variable order integro-differential equations

Abstract: In this research, we study a general class of variable order integro-differential equations (VO-IDEs). We propose a numerical scheme based on the shifted fifth-kind Chebyshev polynomials (SFKCPs). First, in this scheme, we expand the unknown function and its derivatives in terms of the SFKCPs. To carry out the proposed scheme, we calculate the operational matrices depending on the SFKCPs to find an approximate solution of the original problem. These matrices, together with the collocation points, are used to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The above literature showed that the exact solutions of FDEs are usually very hard to acquire or contain some special functions. Therefore, more and more researchers turn to numerical methods, for example finite-difference methods [10][11][12] and spectral methods [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Spectral methods are well-known high-accuracy methods [27][28][29][30][31][32][33][34][35], normally carried out by a Galerkin, Tau, or collocation approach in practical problems.…”
Section: Introductionmentioning
confidence: 99%
“…The above literature showed that the exact solutions of FDEs are usually very hard to acquire or contain some special functions. Therefore, more and more researchers turn to numerical methods, for example finite-difference methods [10][11][12] and spectral methods [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Spectral methods are well-known high-accuracy methods [27][28][29][30][31][32][33][34][35], normally carried out by a Galerkin, Tau, or collocation approach in practical problems.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the authors of [31] used shifted Chebyshev polynomials of the fifth kind in conjunction with the collocation method to obtain approximate solutions for time-fractional partial integro-differential equations. In [32], the authors proposed a numerical scheme based on the shifted fifth-kind Chebyshev polynomials for solving nonlinear variable order integro-differential equations. The authors of [33] used a collocation method based on shifted fifth-kind Chebyshev polynomials to solve a nonlinear variable-order fractional reaction-diffusion equation with a Mittag-Leffler kernel.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the authors in [21] employed the Boubaker wavelets together with the operation matrix of derivative to solve singular initial value problem. The collocation method is presented in [22] based on the second kind Chebyshev wavelets for solving calculus of variation problems. The use of the operational matrices of derivatives and integrals has been highlighted in the field of numerical analysis [23][24][25].…”
Section: Introductionmentioning
confidence: 99%